Fast and Slow Nonlinearities in Epsilon‐Near‐Zero Materials. Issue 2 (28th December 2020) - Khurgin, Jacob B.; Clerici, Matteo; Kinsey, Nathaniel
Abstract: Novel materials, with enhanced light–matter interaction capabilities, play an essential role in achieving the lofty goals of nonlinear optics. Recently, epsilon‐near‐zero (ENZ) media have emerged as a promising candidate to enable the enhancement of several nonlinear processes including refractive index modulation and harmonic generation. Here, the optical nonlinearity of ENZ media is analyzed to clarify the commonalities with other nonlinear media and its unique properties. Transparent conducting oxides as the family of ENZ media with near‐zero permittivity in the near‐infrared (telecom) band are focused on. The instantaneous and delayed nonlinearities are investigated. By identifying their common origin from the band nonparabolicity, it is shown that their relative strength is entirely determined by a ratio of the energy and momentum relaxation (or dephasing) times. Using this framework, ENZ materials are compared against the many promising nonlinear media that are investigated in literature and show that while ENZ materials do not radically outpace the strength of traditional materials in either the fast or slow nonlinearity, they pack key advantages such as an ideal response time, intrinsic slow light enhancement, and broadband nature in a compact platform making them a valuable tool for ultrafast photonics applications for decades to come. Abstract : Epsilon‐near‐zero (ENZ) films are promising nonlinear materials, demonstrating ultrafast unity‐order index modulation and enhanced harmonic generation. Here, these demonstrations are united under a single theoretical framework of "fast" and "slow" nonlinearities that both originate in the conduction band nonparabolicity. Through this, ENZ materials and their trade‐offs are compared to the field to guide future material studies and prospective applications.